Prevalence and risk factors of depression in juvenile systemic lupus erythematosus - Puspitanza, Ika Dian; Alia, Myrna; Kesuma, Yudianita; Rismarini, Rismarini; Novery, Edy; Bahar, Erial (Indonesian Pediatric Society, 2024)
Background Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that affects multiple organ systems, including the central nervous system. Depression is one of the neuropsychiatric manifestations of juvenile SLE . Objective To estimate the prevalence of depressive disorders in juvenile SLE and identify its potential risk factors. Methods This cross-sectional study was conducted in juvenile SLE patients at Dr. Mohammad Hoesin General Hospital, Palembang. Sociodemographic data and medications were recorded. Disease activity of SLE was assessed using the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI). Physical activity was measured using the Physical Activity Questionnaire for Children (PAQ-C) and the Physical Activity Questionnaire for Adolescents (PAQ-A). All subjects were screened for depression using the Childhood Depression Inventory (CDI) questionnaire. Multiple linear regression analyses were used to determine risk factors for depressive disorders. Results We included 72 patients, of whom 67 (93.1%) were female. Mean age of the patients was 12 years 4 months (SD 2 years 6 months); most (67; 93.1%) were 10-18 years of age. Depression was found in 24 patients (33.3%). SLEDAI scores of ?3 (flare) were found in 54 patients (75%) and low physical activity was found in 62 (86.1%) patients. The prevalence of depression based on the Children's Depression Inventory was 33.3%. A SLEDAI score of ?3 and low physical activity were significantly associated with depression (P=0.009 and P=0.025, respectively). On multiple linear regression analysis, only SLEDAI score of ?3 remained significantly associated with depression (P= 0.017; OR 12.6; 95%CI 1.6–101.7). Gender, age, family economic status, father's education, mother's education, family history of depression, and duration of illness were not associated with depression. Conclusion A SLEDAI score indicating flare (?3) and low physical activity are significantly associated with an increased risk of depression. A SLEDAI score is an independent risk factor for depression when all other significant risk factors are considered.